2019
DOI: 10.1158/1078-0432.ccr-18-3755
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter, Open-Label, Phase II Study of Bendamustine and Rituximab Followed by 90-Yttrium (Y) Ibritumomab Tiuxetan for Untreated Follicular Lymphoma (Fol-BRITe)

Abstract: Purpose: Bendamustine and rituximab (BR) has been established as a superior frontline therapy over R-CHOP in the treatment of follicular lymphoma (FL). Yttrium-90 Ibritumomab tiuxetan (90 YIT) is an effective consolidation strategy after chemotherapy induction. This prospective, single-arm, multicenter, phase II trial evaluated the response rate, progressionfree survival (PFS), and tolerability of BR followed by consolidation with 90 YIT in patients with untreated FL. Patients and Methods: The study included g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…At a median follow-up of 45 months, OS and PFS were 96% and 71%, respectively. 9 Although this study included a relatively small number of patients, the high ORR and proportion obtaining CR/CRu, compares favorably to the BRIGHT and StiL studies of 6 cycles of rituximab-bendamustine, demonstrating a CR of 31% and 40%, respectively. 10 , 11 …”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…At a median follow-up of 45 months, OS and PFS were 96% and 71%, respectively. 9 Although this study included a relatively small number of patients, the high ORR and proportion obtaining CR/CRu, compares favorably to the BRIGHT and StiL studies of 6 cycles of rituximab-bendamustine, demonstrating a CR of 31% and 40%, respectively. 10 , 11 …”
Section: Introductionmentioning
confidence: 67%
“…Fol-BRITe was a prospective multicenter trial that evaluated the response rate, PFS, and tolerability of BR followed by consolidation with 90Y-IT in patients with untreated FL. 9 The study included 39 chemotherapy-naïve patients with stages II-IV disease treated with rituximab, 375 mg/m 2 , followed by four 28-day cycles of rituximab 375 mg/m 2 on day 1 and bendamustine 90 mg/m 2 on days 1 and 2. Patients were eligible for consolidation with 90Y-IT, 6-12 weeks later, if they obtained a PR after induction and had adequate count recovery and bone marrow infiltration <25%.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several randomized and non‐randomized trials have demonstrated the utility of 90 Y‐IT as a consolidation therapy after initial FL treatment, including one evaluating the combination with 90 Y‐IT consolidation and rituximab maintenance (Table 4). 3,4,11–16 In addition to these promising results, the data from the BRiZ study demonstrate that patients with FL may also benefit from 90 Y‐IT consolidation, if they can achieve a high‐quality response after second or third‐line immunochemotherapy with BR.…”
Section: Discussionmentioning
confidence: 99%
“…Cetuximab, an anti-epidermal growth factor receptor monoclonal antibody, is a standard option for the treatment of advanced cervical cancer (Meira et al, 2009). Fourteen drugs were identified, including catumaxomab, aldesleukin, trastuzumab, and ibritumomab tiuxetan, all of which have been confirmed for various cancers, including malignant ascites (Kietpeerakool et al, 2019), renal cell carcinoma (Fishman et al, 2019), gastric cancer (Kimura et al, 2018), and lymphoma (Lansigan et al, 2019), respectively. Among drug-interactions obtained, Staurosporine has been reported to target ZAP70 (Overington et al, 2006), but their interaction in cancer research is still blank.…”
Section: Discussionmentioning
confidence: 99%